A new MIR bow shock source in the Galactic center. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Sabha, N.; Zamaninasab, M.; Eckart, A.; Moser, L.
Abstract: We find a convex-like feature at a distance of 0.68 pc (17″) from the position of the supermassive black hole, Sgr A*, at the center of the nuclear stellar cluster. This feature resembles a stellar bow shock with a symmetry axis pointing to the center. We discuss the possible nature of the feature and the implications of its alignment with other dusty comet-like objects inside the central parsec.